Youth, identity, and stigma in the media - Marôpo, Lidia (2018)
This article presents the results of a news audience study with African migrant children and young people in Lisbon’s surroundings. Using qualitative and participatory methodologies in a nine-month study, we analyzed the role of the news in their lives, focusing specifically on their identity construction in light of the often stigmatizing media discourses. We have concluded that the experience of violence in their neighborhoods and the insistent news representation of this violence (perceived by them as the main cause of the community’s negative external image) significantly mark the socialization process of the study group. This contributes to identity constructions that we classify into the following three categories: mistrustful identity, anguished identity, and stigmatized identity.